(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
In the 1990s, the publisher Cia. das Letras promoted the publication of previously unreleased works by Nelson Rodrigues. Among these works was the novel The Wedding, which had originally been published and subsequently censored in 1966. Over 30 years later, in 1997, the novel received its first theatrical adaptation, directed by Antonio Abujamra and João Fonseca, from Cia. Os Fodidos Privilegiados in Rio de Janeiro. The play represented Brazil in 1999 at the XXII FITEI (International Festival of Iberian Expression) in Porto, Portugal, and also at the VII Ibero-American Theater Festival in Bogotá, Colombia, in 2000. The author’s intention was to analyze the process of adaptation of the book for the stage.